High-energy plasma dynamic synthesis of multiphase iron oxides containing Fe3O4 and ?-Fe2O3 with possibility of controlling their phase composition; Journal of Alloys and Compounds; Vol. 774 - Shanenkov I. I. Ivan Igorevich; Sivkov A. A. Aleksandr Anatolyevich; Ивашутенко А. С. Александр Сергеевич; Медведева Т. М. Татьяна Михайловна; Щетинин И. В. Игорь Викторович (2019, 2019)
Title screen